EFISIENSI BIAYA PRODUKSI SEBAGAI PENGENDALIAN BIAYA PRODUKSI PADA PDAM KOTA PAREPARE - Fatimah, Fatimah; M, Samsiar (Universitas Muhammadiyah Parepare, 2019)
This study aims to determine how the efficiency of production costs in the Regional Water Supply Company in the City of Parepare, to determine whether controlling the production costs in the Regional Water Supply Company in the City of Parepare is efficient. The sample selection is part of a number of characteristics possessed by the population used for research. Data collection techniques in this study are quantitative. Data collection is carried out as a whole from the existing accounting field in PDAM Kota Parepare. Descriptive analysis is used to describe the drafting system, control system and the factors that influence the realization of production costs in PDAM Kota Parepare. The results of the study stated that the efficiency of production costs as a control of production costs that exist in PDAM Kota Parepare over the past five years has fluctuated. The results of the five-year assessment were in 2013 an efficiency ratio of 101% with inefficient achievement results, in 2014 an efficiency ratio of 107% with inefficient achievement results, in 2015 an efficiency ratio of 88% with quite efficient achievement results, in 2016 an efficiency ratio of 97% with achievement results are less efficient, in 2017 the efficiency ratio is 94% with achievement results less efficient. The inefficient factor of production costs in PDAM Kota Parepare is due to the expenditure of excessively large expenses and very low income. This shows less efficient in controlling production costs, therefore PDAM Kota Parepare must pay more attention to controlling production costs in terms of making decisions to achieve efficient targets.